Female Breast and Pelvic Exam: A Student-to-Student Guide - Jonathan Peled; David Thompson; Stephanie Trentacoste; Nadine Katz (Association of American Medical Colleges, 2009)
Abstract Physician behaviors that constitute patient-centered examinations are usually modeled informally by preceptors at the bedside. This guide supplements and codifies some of those informal yet critical lessons for medical students learning breast and pelvic exams. Written by second-year medical students-in collaboration with a faculty member in OB/GYN-the guide addresses common points of confusion. Intended as a supplement to textbook chapters and online video tutorials, it can be easily folded into the pockets of students on OB/GYN clerkships or used during physical diagnosis courses as a reference. Included are step-by-step instructions for performing the exam, a list of suggestions for appropriate language, and a sidebar with tips that may not be obvious to students. At our institution, the guide is included in the MS2 physical diagnosis course and is available during the MS3 OB/GYN rotation. It could also be useful to residents from various disciplines while rotating through OB/GYN services. The guide is not intended to replace a textbook chapter but rather to act as a portable reference. One limitation of the guide is that it lacks illustrations, and in future revisions, we plan to include diagrams to illustrate key points. We have received positive anecdotal feedback from students and faculty; an evaluation of the effect of this guide on student attitudes about the pelvic exam as well as its effect on their performance during Observed Structured Clinical Exams (OSCEs) is planned for the near future. We expect the guide to remain useful to students in its current format. Other users and instructors are welcome build upon the guide, and we would be glad to provide the document in Word format to facilitate such endeavors, provided that any improvements include appropriate attribution to the original authors.